Mission to Mars - Jacobson, Tom; De Palma, Brian (Burbank, California Touchstone Home Video, 2000)
The year is 2020, and the first manned mission to Mars, commanded by Luke Graham, lands safely on the red planet. But the Martian landscape harbors a bizarre and shocking secret that leads to a mysterious disaster so catastrophic, it decimates the crew. Haunted by a cryptic last message from Graham, NASA launches the Mars Recovery Mission to investigate and bring back survivors-if there are any. Confronted with nearly insurmountable dangers, but propelled by deep friendship, the team finally lands on Mars and makes a discovery so amazing, it takes your breath away.
Screenplay by Jim Thomas & John Thomas and Graham Yost ; Executive producer, Sam Mercer ; Associate producer, Ted Tally ; Co-producer, David Goyer, Justin Greene, Jim Wedaa ; Production designer, Ed Verreaux.
Tim Robbins, Gary Sinise, Don Cheadle, Connie Nielsen, Jerry O'Connell, Kim Delaney, Elise Neal, Peter Outerbridge, Jill Teed, Kavan Smith.
Dolby digital.
In English.
Keywords: Space flight to Mars -- Drama; Mars (Planet) -- Drama